PELATIHAN INSPECTION PREVENTIVE MAINTENANCE ALAT SPECTROPHOTOMETER UV-VIS UNTUK TEKNISI ELEKTROMEDIS DI PROVINSI RIAU - Hadziqoh, Nur; Surakusumah, Rino Ferdian; Abrarr, Abrarr; Pertiwi, Yeni; Lasiyah, Nani (UNIVERSITAS PGRI MADIUN, 2023)
Abstract. Uv-Vis Spectrophotometer is one of the instruments in the hospital located in the clinical laboratory where its management is under the responsibility of the Electromedical Technician. The medical device technology development has led to adjustments and developments in managing the Uv-Vis spectrophotometer. The purpose of this service activity is to provide Inspection Preventive Maintainance (IPM) training for Uv-Vis spectrophotometer equipment and share developments in Uv-Vis spectrophotometer technology with electromedical technicians. With this, hospitals can provide complete services to the community. The training was held on March 26, 2022, using the Zoom Meeting media and was attended by 401 participants from all over Indonesia. Participants were given a pretest and posttest to determine the level of participants abilities with this training. Before the training, the ability of the participants was 60.30% while after the training the ability of the participants was 78.55% so there was an increase in the ability of the participants by 18.25%. The average level of participant satisfaction with this training activity is 85.54%, which is in the very satisfactory category Abstrak. Spektrofotometer Uv-Vis merupakan salah satu alat di rumah sakit yang berada pada laboratorium klinik dimana pengelolaannya di bawah tanggung jawab Teknisi Elektromedis. Perkembangan teknologi alat kesehatan menyebabkan adanya penyesuaian dan perkembangan terhadap pengelolaan alat spektrofotometer Uv-Vis. Tujuan dari kegiatan pengabdian ini adalah memberikan pelatihan Inspection Preventive Maintainance (IPM) peralatan spektrofotometer Uv-Vis dan sharing perkembangan teknologi spektrofotometer Uv-Vis kepada teknisi elektromedis. Dengan hal itu, rumah sakit dapat memberikan pelayanan yang paripurna kepada masyarakat. Pelatihan dilaksanakan pada tanggal 26 maret 2022 menggunakan media Zoom Meeting dan diikuti oleh 401 peserta dari seluruh Indonesia. Peserta diberikan pretest dan postest unutk mengetahui tingkat kemampuan peserta dengan adanya pelatihan ini. Sebelum pelatihan kemampuan peserta sebesar 60,30% sedangkan setelah pelatihan kemampuan peserta sebesar 78,55% sehingga terjadi peningkatan kemampuan peserta sebesar 18,25%. Adapun rata-rata tingkat kepuasan peserta terhadap kegiatan pelatihan ini adalah 85,54% berada pada kategori sangat memuaskan.